Pre-heating by defocusation of the CO2-Laser polishing beam: an experimental report from the lab-floor -INVITED - Bliedtner Jens (EDP Sciences, 2021)
The laser beam polishing for glass and plastics is a purely thermal process and melts the ground or lapped structures to a depth of limited extent. This results in a smoothing of the surface, whereby the 1st - 4th order shape deviations can be corrected very well and transparent surfaces are created. The process is excellently suited for quartz glasses and other optical glasses with a low coefficient of expansion α. Furthermore, thermoplastics or metallic molds for injection molding and precision molding applications can also be polished with the laser beam. On the other hand, special measures are required for glasses with a high α, e.g. preheating of the component. For the investigations, a defocused laser beam was used for the defined preheating of glasses with high linear expansion coefficients. After reaching the material-specific preheating temperature, the laser beam was focused and the polishing process started. A defined cooling process follows again with a defocused beam. In this way, a ground biconvex lens made of boron crown glass was successfully polished. The laser-polished surfaces have an RMS value of 1- 3 nm. The polishing process can be used very flexibly. Likewise, very differently shaped optical components can be polished. The newly developed polishing regime is transferable to other optical glasses with high linear expansion coefficients.